Quantum efficiency of europium doped LaPO4 phosphors for UV sensing applications - Sadowska, Karolina; Awramiuk, Paweł; Zgłobicka, Izabela; Rećko, Katarzyna; Żmojda, Jacek (Photonics Letters of Poland, 2022)
The radiation conversion phenomenon is used for UV sensing applications with rare earth doped phosphors. This paper presents the results of structural and optical measurements of undoped and europium doped LaPO4 phosphors. LaPO4 phosphors with 1% mol, 2% mol, and 5% mol of europium were fabricated by the co-precipitation method. The effect of Eu3+ concentrations on the luminescence characteristics under UV LED excitation was investigated. The maximum quantum efficiency of luminescence (c.a. 82%) was obtained in sampled doped with 5% of europium. Full Text: PDF References M. Runowski, "Nanotechnologia – nanomateriały, nanocząstki i wielofunkcyjne nanostruktury typu rdzeń/powłoka", Chemik 68, 9, 766-775 (2014). DirectLink J. Zhou, J.L. Leano Jr., Z. Liu, D. Jin, K.-L. Wong, R.S. Liu, et al., "Impact of Lanthanide Nanomaterials on Photonic Devices and Smart Applications", Small 14, 1801882 (2018). CrossRef Z. Li, Y. Zhang, G. Han, "Lanthanide-Doped Upconversion Nanoparticles for Imaging-Guided Drug Delivery and Therapy", Springer Series in Biomater. Sci. Eng. 6, 139-164, (2016). CrossRef M. Lin, Y. Zhao, S. Wang, M. Liu, Z. Duan, Y. Chen, et al., "Recent advances in synthesis and surface modification of lanthanide-doped upconversion nanoparticles for biomedical applications", Biotechnol. Adv. 30, 1551-1561 (2012). CrossRef H. Su, Y. Nie, H. Yang, D. Tang, K. Chen, T. Zhang, "Improving the thermal stability of phosphor in a white light-emitting diode (LED) by glass-ceramics: Effect of Al2O3 dopant", J. Eur. Ceram. Soc. 38, 2005-2009 (2018). CrossRef J. Huang, X. Hu, J. Shen, D. Wu, C. Yin, R. Xiang, et al., "Facile synthesis of a thermally stable Ce3+:Y3Al5O12 phosphor-in-glass for white LEDs", Cryst. Eng. Comm 17, 7079-7085 (2015). CrossRef R. Zhang, H. Lin, Y. Yu, D. Chen, J. Xu, Y. Wang, "A new-generation color converter for high-power white LED: transparent Ce3+:YAG phosphor-in-glass", Laser Photon. Rev. 8, 158-164 (2014). CrossRef B. Zheng, Y. Bai, H. Chen, H. Pan, W. Ji, X. Gong, et al., "Near-Infrared Light-Excited Upconverting Persistent Nanophosphors in Vivo for Imaging-Guided Cell Therapy", ACS Appl. Mater. Interfaces 10, 19514 (2018). CrossRef J. Qiao, G. Zhou, Y. Zhou, Q. Zhang, Z. Xia, "Divalent europium-doped near-infrared-emitting phosphor for light-emitting diodes", Nature Communications 10 (1), 5267 (2019). CrossRef V. Singh, A. Kumar, C. Mehare, H. Jeong, S. Dhoble, "UV/VUV excited photoluminescence of Tb3+ doped LaPO4 green emitting phosphors for PDP applications", Optik 206, 163733 (2020). CrossRef G. Han, Y. Wang, C. Wu, J. Zhang, "Hydrothermal synthesis and vacuum ultraviolet-excited luminescence properties of novel Dy3+-doped LaPO4 white light phosphors", Mat. Res. Bull. 44 (12), 2255-2257 (2009). CrossRef K. S. Gupta, P. S. Ghosh, M. Sahu, K. Bhattacharyya, R. Tewari, V. Natarajan, "Intense red emitting monoclinic LaPO4:Eu3+ nanoparticles: host–dopant energy transfer dynamics and photoluminescence properties", RSC Adv. 5, 58832-58842 (2015). CrossRef